An improved contact modification routine for a computationally efficient CFD simulation of packed beds - Martin Kutscherauer (Elsevier, 2022)
Particle-resolved computational fluid dynamics (PRCFD) is the most detailed modeling approach for fixed bed reactors. A major issue of PRCFD is to ensure a high quality of the underlying 3D calculation mesh around the particle-particle and particle-wall contacts, which otherwise results in convergence problems. A still unresolved challenge, especially for packed beds of non-spherical particles, is to avoid this poor-quality mesh at contacts by modification of the packed bed geometry, while providing a reasonable number of mesh cells and physical accuracy. Based on the so called local caps method, a novel mesh-type independent routine was developed to modify all occurring contacts of a packed bed of rings and to generate a computationally efficient high-quality mesh. Thereby, one of the two particles involved in a point or line contact was inflated and used as cap geometry, whereas area contacts were combined via the contact surface. The impact of the cap size on mesh quality, packed bed structure, fluid flow and heat transport was investigated for a technically relevant slender packed bed under various conditions. For a small ratio between solid and fluid thermal conductivity (λPλF≤23.1), and ReP=50−600, a cap size smaller than 0.8% of the outer particle diameter did not have significant impact on the simulation results. To apply the approach to other packing structures and particle shapes, it is recommended to investigate at least three different cap sizes to determine at which cap size the independence from contact modification is achieved.